Religion and Culture in Social Transformation of Subang North Coast Community - Agus Maksum; M. Yusuf Wibisono; Deni Miharja (UIN Sunan Gunung Djati Bandung, 2022)
The presence of the port certainly impacts the Patimban community, ranging from positive and negative impacts. Furthermore, besides physical effects, psychological consequences must be observed and investigated from religion, culture, environmental change, and social transformation. The purpose of this study was to analyze the views of the Patimban community on the north coast of Subang in interpreting the dimensions of belief, the sizes of experience, the dimensions of social consequences, and resistance and accommodation to social change in Islam and religious practices in a life that is in synergy with culture. The results of this study indicate that the views of the Patimban community on the northern coast of Subang in interpreting resistance and accommodation to social change, in terms of resistance to the peculiarities of social interaction in rural models in Patimban, are gradually fading and changing with the interaction patterns of urban models. However, it is still difficult to let go of identity as a rural community with its various characteristics in specific contexts.